A new species of subgenus Asonicogryllus He, 2019 from Yunnan (Orthoptera: Gryllidae: Gryllinae) - Xu, Jing-Yi; Liu, Yi-Jiao; Li, Shi-Yu; He, Zhu-Qing (Zootaxa, 2021)
We studied the relationship of the genera Loxoblemmus Saussure, 1877 and Asonicogryllus He, 2019 by reconstructing the phylogenetic tree based on 2 mitochondrial genes and 2 ribosomal genes. The result shows that Loxoblemmus is paraphyletic. Thus, we place Asonicogryllus as a subgenus of Loxoblemmus. Meanwhile, we report a new species of Asonicogryllus, L. (A.) bronzus He sp. nov. The new species is similar to L. (A.) kwanghua, but it has well developed forewings and hindwings. The type specimens are deposited in the Museum of Biology, East China Normal University (ECNU).